Pumps and Prompts for Gist Explanations in Tutorial Dialogues About Breast Cancer. Issue 1 (2nd January 2018) - Wolfe, Christopher R.; Reyna, Valerie F.; Widmer, Colin L.; Cedillos-Whynott, Elizabeth; Weil, Audrey M.; Brust-Renck, Priscila G.
Abstract : Fuzzy-Trace Theory (FTT) generalizes research on discourse to predict how health messages can be better understood and remembered, thereby influencing decision making. Applying FTT, BRCA Gist delivers messages interactively through tutorial dialogues and is the first Intelligent Tutoring System designed to help laypeople make sound medical decisions. Previous research indicates that BRCA Gist helps people form useful "gist explanations, " which leads to improved knowledge, comprehension, and risk assessment. The present research examined the effectiveness of different BRCA Gist dialogue moves, including general pumps for information and prompts for specific information. Participants were randomly assigned to a control group or one of four BRCA Gist conditions evoking gist or verbatim representations crossed with general pumps or specific information prompts. Gist-evoking pumps by themselves produced significant gains in knowledge and risk assessment. Specific verbatim prompts increased knowledge without affecting risk assessment. Results are explained in light of memory research and FTT principles.